The fair premium test for life insurance - Bai, Jiangna (2006)
Annuity insurers were making losses by underestimating mortality improvement. If the same projection fault occurs for term assurance policies, life insurers writing term assurance policies were likely to have benefited from the improving mortality and the profit could be significant in comparison with annuities. This dissertation uses quantitative research method by developing cash flows for term policies and using the moneys worth ratio and profit ratio to test the policys profitability.